Education and Action Movement of Climate Smart Agriculture Farmers: Adapting and Mitigating the Impacts of Climate Change on Agricultural Peatland in Perigi Village - Dessy Adriani; Muhammad Yazid; Muhammad Yamin; Muhammad Andri Zuliansyah; Serly Novitasari; Siti Ramadhani Andhelia; M. Huanza; Dini Damayanthi; Trisna Wahyu Swasdiningrum Putri (Unram Journal of Community Service, 2025)
The agricultural sector's sustainability is seriously threatened by climate change, especially in vulnerable places like Perigi Village, which is primarily made up of peatlands. Due to a lack of knowledge about climate change adaptation and mitigation, farmers face decreasing productivity, seasonal uncertainty, and the risk of land fires. Through training, outreach, technical support, and the use of basic technologies based on climate-smart agriculture, the Climate-Smart Agriculture Farmers Education and Action Movement programme seeks to increase farmer capacity. Extension, hands-on training, agrosilvofishery systems, educational media, and the formation of Climate-Smart Agriculture Farmers Groups are some of the techniques employed. The program's results demonstrate a significant increase in farmer knowledge, the ability to apply adaptive techniques, and the creation of regional organisations that support collective efforts to reduce climate risks. This activity has an educational, social, ecological, and economic impact on the community and can be replicated as a model for village empowerment. This curriculum emphasises the importance of collaboration between academics, village administrations, and farmers in order to create sustainable agriculture and community resilience to climate change.